2021
DOI: 10.3389/fonc.2021.783575
|View full text |Cite
|
Sign up to set email alerts
|

NK4 Regulates Laryngeal Squamous Cell Carcinoma Cell Properties and Inhibits Tumorigenicity by Modulating the DKK1/Wnt/β-Catenin Axis

Abstract: ObjectiveTo investigate the effects of NK4 gene on the properties and tumorigenicity in laryngeal squamous cell carcinoma cell.MethodsHere, we used the attenuated Salmonella carrying the NK4 gene to transfect the AMC-HN-8 cells and detected the expression of NK4 by the real-time quantitative polymerase chain reaction (q RT-PCR). The properties of NK4 gene was determined by MTT method, cell scratch test, and flow cytometry. A nude mouse tumorigenesis model was used to evaluate the effect of NK4 gene on the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…27 The DKK1-Wntβ-catenin signaling axis is negatively regulated by the NK4 gene in HNSCC, thus mediating the occurrence and development of HNSCC. 28 DKK1 can also activate the Wntplanar cell polarity pathway to promote neuronal death in Alzheimer's disease. 29 However, the mechanism of DKK1 and PNI remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The DKK1-Wntβ-catenin signaling axis is negatively regulated by the NK4 gene in HNSCC, thus mediating the occurrence and development of HNSCC. 28 DKK1 can also activate the Wntplanar cell polarity pathway to promote neuronal death in Alzheimer's disease. 29 However, the mechanism of DKK1 and PNI remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulated expression of DKK1 in colorectal cancer can inhibit CD8 + T cells through the GSK3β–E2F1–T‐BET pathway and promote malignant progression of cancer cells 27 . The DKK1–Wnt–β‐catenin signaling axis is negatively regulated by the NK4 gene in HNSCC, thus mediating the occurrence and development of HNSCC 28 . DKK1 can also activate the Wnt‐planar cell polarity pathway to promote neuronal death in Alzheimer's disease 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Researches have revealed that DDK1 is over-expressed in LSCC tissues and can be served as an unfavorable survival predictor, which may be a promising therapeutic target for LSCC patients. 38 , 39 Another IRG, namely, interleukin 1 receptor accessory protein (IL1RAP), acts as an IL1R co-receptor to mediate the activation of IL-1 responsive genes. 40 In recent years, many researchers have found that IL1RAP as a key tumor-associated antigen might be used as an immunotherapy target.…”
Section: Discussionmentioning
confidence: 99%